Twitter as an Information Dissemination Source for Delivering Crisis Information during the Outbreak of the COVID-19 Pandemic - Altayar, Mohammed (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2025)
This study aims to investigate the use of Twitter by Saudi government agencies as an information dissemination source to communicate COVID-19-related information. A total of 8,718 tweets from 33 government agencies were collected during a nine-month period from 1 January to 30 September 2020. The results show that Twitter played a dominant role in the crisis communication process. In addition, providing instructions and adjusting information, as well as management reputation, was a basic strategy to respond to the COVID-19 crisis. Furthermore, communication in terms of topics, actors, style, tones and quantity has changed during different phases of the crisis. The study argues that a centralized and highly organized government structure is particularly important in driving an information and communication strategy to tackle the pandemic, and it helps deliver messages with a common identity that promotes extensive public and government interaction.